Surgical treatment of cutaneous fibrosarcoma in a Paint Horse mare: case report - Daneze, Edmilson Rodrigo [UNESP]; de Toledo, Carmen Zilda Pereira [UNESP]; de Lima, Marina Ragagnin [UNESP]; da Rosa Sobreira, Márcia Ferreira [UNESP] (Medicina Veterinaria (UFRPE), 2022)
Fibrosarcomas are primary malignant mesenchymal neoplasia’s of low incidence in horses that sporadically produces metastases. The use of complementary exams such as imaging and aspiration cytology are relevant to identify the lesion and tissues, however, histopathological examination is the method of choice for the conclusive diagnosis. In this sense, the present study reports a case of a fibrosarcoma in a mare. A veterinary consultation was requested due to the development of a mass craniolateral to the right mammary gland in a nine-year-old Paint Horse mare. On palpation, the mass was described as circumscribed, firm consistency and adhered to abdominal muscles. Surgical excision of the neoformation was elected as a form of treatment, the procedure was performed with wide margins. It was observed, during the surgical procedure, that the mass had no continuity to the breast tissue, however there was a small area of adhesion in the abdominal muscle tissues. The excised material was sent for histopathological analysis, as a result, neoplastic mesenchymal proliferation compatible with fibrosarcoma was identified. This patient was followed up periodically for two years after the procedure, and, along this period there was no recurrence at the surgical site nor neoplastic tissues on distant tissues. Therefore, we conclude that early care, surgical excision with wide margins, histopathological identification and periodic follow-up were essential for the successful treatment of the patient.
Tratamento cirúrgico de fibrossarcoma cutâneo em uma égua Paint Horse: relato de caso
Keywords: equine; histopathological diagnosis; neoplasia; skin; surgery